Recommended Protocols for Instrumental Assessment of Voice: American Speech-Language-Hearing Association Expert Panel to Develop a Protocol for Instrumental Assessment of Vocal Function - Patel, Rita R.; Awan, Shaheen N.; Barkmeier-Kraemer, Julie; Courey, Mark; Deliyski, Dimitar; Eadie, Tanya; Paul, Diane; Švec, Jan G.; Hillman, Robert (American journal of speech-language pathology, 2018)
The aim of this study was to recommend protocols for instrumental assessment of voice production in the areas of laryngeal endoscopic imaging, acoustic analyses, and aerodynamic procedures, which will (a) improve the evidence for voice assessment measures, (b) enable valid comparisons of assessment results within and across clients and facilities, and (c) facilitate the evaluation of treatment efficacy. Existing evidence was combined with expert consensus in areas with a lack of evidence. In addition, a survey of clinicians and a peer review of an initial version of the protocol via VoiceServe and the American Speech-Language-Hearing Association's Special Interest Group 3 (Voice and Voice Disorders) Community were used to create the recommendations for the final protocols. The protocols include recommendations regarding technical specifications for data acquisition, voice and speech tasks, analysis methods, and reporting of results for instrumental evaluation of voice production in the areas of laryngeal endoscopic imaging, acoustics, and aerodynamics. The recommended protocols for instrumental assessment of voice using laryngeal endoscopic imaging, acoustic, and aerodynamic methods will enable clinicians and researchers to collect a uniform set of valid and reliable measures that can be compared across assessments, clients, and facilities.